Resilience of a person with various traumatic experiences - Sharipova, Daria R. (Journal of the Belarusian State University. Philosophy and Psychology, 2023)
The definition of resilience in psychology is expanded. The definitions of resilience by different authors are analysed, and the general characteristics of resilience are highlighted. The structural model of resilience is described, and the psychological factors of resilience are highlighted. New characteristics of the personality with various traumatic experiences are highlighted, as well as ways to cope with them through the components of resilience: involvement, control, risk-taking. Three techniques for dealing with traumatic experiences in the context of resilience are presented. The features of the resilience of a person with various traumatic experiences are revealed using the case studies presented. The psychological factors of choosing a particular (resilient or victim) way of coping with traumatic experience are revealed.